Health educational needs assessment and curriculum development for formal adolescent education in human sexuality and family life (1989)
The experiences from various social and health service centres in Nigeria indicate a rising incidence of sex-related disorders among our youths. Evidence suggest that at the basis of these problems are both ignorance on the part of the youths as well as other deficiencies in adolescent youth development caused by the current industrial ‘development in the country, with is attendant effect on the stability of family life and the erstwhile established (traditional) child upbringing patterns. This study assesses the programme developed over the proceeding 4 years by the authors in response to the above problems in adolescent development in Nigeria. It shows that the present programme meets 88.7% of the sex educational needs of these youths studied, this being 92.5% of all those who answered this particular question in the study. The historical development of the curriculum, programme format, course content and other findings of the study are presented and discussed. Based on the findings, recommendations are made towards the development of locally relevant sex education programmes for the Nigerian and other sociologically similar groups of youths.